Acneiform Lesions but not Acne after Treatment with Janus Kinase Inhibitors: Diagnosis and Management of Janus Kinase-acne - Fabienne Ballanger; Nicole Auffret; Marie-Thérèse Leccia; Jean Paul Claudel; Brigitte Dréno (Acta Dermato-Venereologica, 2023)
Abstract is missing (Short communication)